The impact of food-hygiene practices, leadership effectiveness, and spiritual intelligence towards Program Latihan dan Khidmat Negara (PLKN) foodservice performance / Mazni Saad - Saad, Mazni (2016)
Food poisoning cases in the National Service and Training Programme (PLKN) camps are on the rise for over 10 consecutive years despite measures taken by responsible parties and therefore require further attention. Specifically, an unchanged pattern of foodborne incidence has triggered an alarming question on the sustainable operation of food service business in these camps. The objectives of this study are to (i) assess the Food-hygiene Practices of food handlers at PLKN, (ii) to analyse the relationship between Leadership Effectiveness, Food-hygiene Practices, and Spiritual Intelligence (SQ) and (iii) to investigate the impact of these study variables; Leadership Effectiveness, Food-hygiene Practices, and SQ on PLKN's Foodservice Performance. The existing level of Food-hygiene Practices was assessed through questionnaire, interview, and observation, as well as microbial sampling experiments. The questionnaire also assessed the relationship and impact of the four parameters of the study (Leadership Effectiveness, Food-hygiene Practices, SQ, and Foodservice Performance). The survey yielded 87.80% responses from 81 operating camps in Malaysia and provided 1026 usable datasets. Six sets of interviews were conducted among the supervisory personnel of the PLKN camps. For empirical data, 288 microbiological samplings of food-contact surfaces (FCS) and 36 drinking water sources were conducted. The data was analysed using the partial least square and appropriate statistic tools. The microbial analyses failed to correlate with the cleanliness survey, but were consistent with food poisoning outbreaks in the camps. FCS with flat open surfaces such as cutting boards and food trays were found exposed to secondary contamination during the drying and storing stage. They were also prone to transferable bacterial contaminants, thus regular washing and rinsing with hot water is necessary to improve the level of effective cleaning. The camp operators can conduct hygiene control tests independently using a simple microbial swab kit as suggested by this study. An adequate number of food handlers per trainees for every meal session should be reconsidered by the camp operators. This study significantly proved that an effective foodservice manager evokes positive feelings among the food handlers to form a situation of continuous well-being during routine practices. At empirical level, the established interconnectedness between the spiritual and practical person and his/her work applications and expectations underlie and support their thoughts of self-development and success at work. Producing and presenting quality food and services reflects a sense of obligation in helping others through correct practices, while keeping account of one's good deeds for the benefit of one's journey towards the next life. Out of 17 tested hypotheses, SQ Holistic and SQ Challenge failed to reject the null hypotheses in favour to our research hypotheses for food performance. With the large and valid datasets, the positive results showed that the model proposed in this study could be generalized to the routine practices-and performances of other foodservice institutions. Overall, this study has successfully achieved its objectives. The results provide suggestions for PLKN foodservice to develop at a significant level, to be profitable while satisfying customers by meeting their expectations and preferences in healthy food consumption, and to face present challenges while remaining competitive in an increasingly aggressive world.